2013
DOI: 10.1016/j.jip.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Tsetse-Wolbachia symbiosis: Comes of age and has great potential for pest and disease control

Abstract: Tsetse flies (Diptera: Glossinidae) are the sole vectors of African trypanosomes, the causative agent of sleeping sickness in human and nagana in animals. Like most eukaryotic organisms, Glossina species have established symbiotic associations with bacteria. Three main symbiotic bacteria have been found in tsetse flies: Wigglesworthia glossinidia, an obligate symbiotic bacterium, the secondary endosymbiont Sodalis glossinidius and the reproductive symbiont Wolbachia pipientis. In the present review, we discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 149 publications
(205 reference statements)
5
43
0
1
Order By: Relevance
“…A simple check showed that a majority of the 725 "Ca. Arsenophonus" protein-coding genes returned the best or second-best BLAST hits corresponding to the genus Arsenophonus (664) or the closely related genera Providencia, Proteus, Photorhabdus, and Xenorhabdus (16). Eighteen hypothetical proteins did not return any hit; for 27 of the remaining genes phylogenetic affinity is less clear and will require more detailed phylogenetic analysis.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple check showed that a majority of the 725 "Ca. Arsenophonus" protein-coding genes returned the best or second-best BLAST hits corresponding to the genus Arsenophonus (664) or the closely related genera Providencia, Proteus, Photorhabdus, and Xenorhabdus (16). Eighteen hypothetical proteins did not return any hit; for 27 of the remaining genes phylogenetic affinity is less clear and will require more detailed phylogenetic analysis.…”
Section: Figmentioning
confidence: 99%
“…Both symbionts are vertically transmitted via milk glands (7,9,10) and are presumed to compensate for the nutritionally unbalanced blood diet (11)(12)(13)(14)(15). This highly specific microbiome of tsetse flies is usually accompanied by reproductive manipulators from the genus Wolbachia (16) and a diversity of other transient bacteria of unknown relationship to the host (17,18). In contrast to Glossinidae, the family Hippoboscidae is a species-rich, highly diversified, and cosmopolitan group feeding on mammals and birds (4).…”
mentioning
confidence: 99%
“…One trypanosome control strategy that relies on symbiont interactions is known as paratransgenesis (for more details, see references 25, 26, and 125). Paratransgenesis involves manipulating Sodalis to express antitrypanosomal effector molecules and utilizes the cytoplasmic incompatibility properties of Wolbachia (59,126) to drive the genetically modified symbiont into natural populations.…”
Section: Understanding the Tsetse Holobiont For Enhanced Vector Controlmentioning
confidence: 99%
“…Although the presence of Wolbachia has been reported in a limited number of tsetse flies samples (Cheng et al, 2000; O’Neill et al, 1993), a thorough investigation for the presence of this symbiont, particularly in natural populations, as well the genotyping of these infections was lacking. One of the specific objectives of this CRP was to study the prevalence, genotyping and phylogenetic analysis of Wolbachia infections in both laboratory and natural populations of Glossina species including the investigation of the potential reproductive effects this infection may have in tsetse flies (see Doudoumis et al 2013; Wang et al 2013, Schneider et al 2013; (Alam et al, 2012; Doudoumis et al, 2012). …”
Section: Current Statusmentioning
confidence: 99%